1998
DOI: 10.2172/290889
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved infrared studies of C-H bond activation by organometallics

Abstract: ' Lhe Govermient reserves for itself and others acting on its behalf a ruyalty free, nonexclusive, irrev-le, world-wide license for governmental purpses to publish, distribute, translate, duplicate, exhibit, and perform a q such data aopyrighted by the amtractor.The U.S. Department of Energy has the right to use this document for any purpose whatsoever, including the right to reproduce all or any part thereof. Much of the study of these C-H activation reactions has focussed on the spectroscopy of the CO ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It was found that the time scale of the final activation step is similar to that observed in linear alkanes. Analogous results were obtained in mixed linear/cyclic alkane solvents: the observed product formation time scale is reduced by ∼50% in a solution of 0.1 mol fraction n -pentane in cyclopentane relative to the product formation time scale in neat cyclopentane …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…It was found that the time scale of the final activation step is similar to that observed in linear alkanes. Analogous results were obtained in mixed linear/cyclic alkane solvents: the observed product formation time scale is reduced by ∼50% in a solution of 0.1 mol fraction n -pentane in cyclopentane relative to the product formation time scale in neat cyclopentane …”
Section: Resultssupporting
confidence: 75%
“…The formation of the product in the linear alkane solvent has a much faster growth of less than 110 ns, and an intermediate η 2 species is difficult to observe . Nanosecond experiments in n -hexane and cyclohexane show a faster formation of the product in the linear alkane as compared to the cyclic counterpart . Using simple transition state theory, the corresponding free energy barrier for the activation step may be estimated as lying between 6.0 and 7.8 kcal/mol for linear alkanes and 8.4 kcal/mol for C−H activation of cyclic hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%